COLLABORATIVE GOVERNANCE MODEL: A STUDY OF VILLAGE FUND MANAGEMENT IN THE CONTEXT OF VILLAGE AUTONOMY - Mustakim, Mustakim (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Village funds are a fiscal policy specifically provided to village governments to support broad village autonomy. Demands for collaboration among stakeholders have emerged for implementation in various public organizations, one of which is village government. However, the implementation of collaboration has not been optimal, resulting in suboptimal management, low human resource capacity, and minimal transparency and oversight, resulting in misuse of village funds. This study was conducted to determine the collaboration process and the driving and inhibiting factors in village fund management. The study was qualitative and descriptive. Primary data were obtained through a series of observations and in-depth interviews with key stakeholders in village fund management. Secondary data were obtained through official documentation issued by relevant agencies. The research instrument used was theory collaborative governanceby Ansell and Gash (2008) which includes (1) Initial conditions, (2) Facilitative leadership, (3) Institutional design, (4) Collaborative process. The research results show that the collaborative process in the management of village funds that has been implemented has not run optimally. Therefore, improvements are needed from the village government as the implementer of village fund management to implement better collaborative governance so that village fund management can run effectively and efficiently.